Cyclin-Dependent Kinase 8 Represents a Positive Regulator of Cytomegalovirus Replication and a Novel Host Target for Antiviral Strategies - Obergfäll, Debora; Wild, Markus; Sommerer, Mona; Barillas Dahm, Malena; Kicuntod, Jintawee; Tillmanns, Julia; Kögler, Melanie; Lösing, Josephine; Dhotre, Kishore; Müller, Regina; Wangen, Christina; Wagner, Sabrina; et al. (Pharmaceutics, 2024)
Background. Cyclin-dependent kinase 8 (CDK8) is a multifaceted regulator and represents a catalytic component of the transcriptional Mediator complex. CDK8 activity, on the one hand, increases transcriptional elongation by the recruitment of Mediator/super elongation complexes, but, on the other hand, negatively regulates CDK7-controlled transcriptional initiation through inactivating cyclin H phosphorylation. Recently, these combined properties of CDK8 have also suggested its rate-limiting importance for herpesviral replication. Objectives. In this paper, we focused on human cytomegalovirus (HCMV) and addressed the question of whether the pharmacological inhibition or knock-down of CDK8 may affect viral replication efficiency in cell culture models. Methods. A number of human and animal herpesviruses, as well as non-herpesviruses, were used to analyze the importance of CDK8 for viral replication in cell culture models, and to assess the antiviral efficacy of CDK8 inhibitors. Results. Using clinically relevant CDK8 inhibitors (CCT-251921, MSC-2530818, and BI-1347), HCMV replication was found strongly reduced even at nanomolar drug concentrations. The EC50 values were consistent for three different HCMV strains (i.e., AD169, TB40, and Merlin) analyzed in two human cell types (i.e., primary fibroblasts and astrocytoma cells), and the drugs comprised a low level of cytotoxicity. The findings highlighted the following: (i) the pronounced in vitro SI values of anti-HCMV activity obtained with CDK8 inhibitors; (ii) a confirmation of the anti-HCMV efficacy by CDK8–siRNA knock-down; (iii) a CDK8-dependent reduction in viral immediate early, early, and late protein levels; (iv) a main importance of CDK8 for viral late-stage replication; (v) several mechanistic aspects, which point to a strong impact on viral progeny production and release, but a lack of CDK8 relevance for viral entry or nuclear egress; (vi) a significant anti-HCMV drug synergy for combinations of inhibitors against host CDK8 and the viral kinase vCDK/pUL97 (maribavir); (vii) finally, a broad-spectrum antiviral activity, as seen for the comparison of selected α-, β-, γ-, and non-herpesviruses. Conclusions. In summary, these novel data provide evidence for the importance of CDK8 as a positive regulator of herpesviral replication efficiency, and moreover, suggest its exploitability as an antiviral target for novel strategies of host-directed drug development.
CRIS-Team Scopus Importer:2024-10-04
Keywords: antiviral approach with CDK8-inhibitory small molecules; broad-spectrum antiviral CDK8 inhibitors; cyclin-dependent kinase 8 (CDK8); human cytomegalovirus (HCMV); human pathogenic herpesviruses; negative impact of CDK8 inhibitors; novel host-directed targeting strategies; regulation of viral replication; siRNA-mediated CDK8 knock-down; virus-supportive cellular protein kinases

Cytomegalovirus cyclin-dependent kinase ortholog vCDK/pUL97 undergoes regulatory interaction with human cyclin H and CDK7 to codetermine viral replication efficiency - Schütz, Martin; Wangen, Christina; Sommerer, Mona; Kögler, Melanie; Eickhoff, Jan; Degenhart, Carsten; Klebl, Bert; Naing, Zin; Egilmezer, Ece; Hamilton, Stuart T.; Rawlinson, William D.; Sticht, Heinrich; et al. (Virus Research, 2023)
Human cytomegalovirus (HCMV) infection is shaped by a tightly regulated interplay between viral and cellular proteins. Distinct kinase activities, such as the viral cyclin-dependent kinase ortholog (vCDK) pUL97 and cellular CDK7 are both crucial for efficient viral replication. Previously, we reported that both kinases, vCDK/pUL97 and CDK7, interact with cyclin H, thereby achieving an enhanced level of kinase activity and overall functionality in viral replication. Here we provide a variety of novel results, as generated on a methodologically extended basis, and present a concept for the codetermination of viral replication efficiency through these kinase activities: (i) cyclin H expression, in various human cell types, is substantially upregulated by strains of HCMV including the clinically relevant HCMV Merlin; (ii) vCDK/pUL97 interacts with human cyclin H in both HCMV-infected and plasmid-transfected cell systems; (iii) a doxycycline-inducible shRNA-dependent knock-down (KD) of cyclin H significantly reduces pUL97 activity (qSox in vitro kinase assay); (iv) accordingly, pUL97 in vitro kinase activity is seen significantly increased upon addition of recombinant cyclin H; (v) as a point of specific importance, human CDK7 activity shows an increase by vCDK/pUL97-mediated trans-stimulation (whereas pUL97 is not stimulated by CDK7); (vi) phosphosite-specific antibodies indicate an upregulated CDK7 phosphorylation upon HCMV infection, as mediated through a pUL97-specific modulatory effect (i.e. shown by pUL97 inhibitor treatment or pUL97-deficient viral mutant); (vii) finally, an efficient KD of cyclin H in primary fibroblasts generally results in an impaired HCMV replication efficiency as measured on protein and genomic levels. These results show evidence for the codetermination of viral replication by vCDK/pUL97, cyclin H and CDK7, thus supporting the specific importance of cyclin H as a central regulatory factor, and suggesting novel targeting options for antiviral drugs.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Codetermination of viral replication; Cyclin H knock-down; Functional importance of cyclin H; Human cytomegalovirus; Modulation of vCDK/pUL97 activity in vitro; Options for antiviral drug targeting; pUL97-mediated CDK7 trans-stimulation; vCDK/pUL97–cyclin binding; Viral cyclin-dependent kinase (CDK) ortholog

Orally bioavailable RORγ/DHODH dual host-targeting small molecules with broad-spectrum antiviral activity - Herrmann, Alexandra; Gege, Christian; Wangen, Christina; Wagner, Sabrina; Kögler, Melanie; Cordsmeier, Arne; Irrgang, Pascal; Ip, Wing Hang; Weil, Tatjana; Hunszinger, Victoria; Groß, Rüdiger; Heinen, Natalie; et al. (Antiviral Research, 2024)
Host-directed antivirals (HDAs) represent an attractive treatment option and a strategy for pandemic preparedness, especially due to their potential broad-spectrum antiviral activity and high barrier to resistance development. Particularly, dual-targeting HDAs offer a promising approach for antiviral therapy by simultaneously disrupting multiple pathways essential for viral replication. Izumerogant (IMU-935) targets two host proteins, (i) the retinoic acid receptor-related orphan receptor γ isoform 1 (RORγ1), which modulates cellular cholesterol metabolism, and (ii) the enzyme dihydroorotate dehydrogenase (DHODH), which is involved in de novo pyrimidine synthesis. Here, we synthesized optimized derivatives of izumerogant and characterized their antiviral activity in comparison to a recently described structurally distinct RORγ/DHODH dual inhibitor. Cell culture-based infection models for enveloped and non-enveloped DNA and RNA viruses, as well as a retrovirus, demonstrated high potency and broad-spectrum activity against human viral pathogens for RORγ/DHODH dual inhibitors at nanomolar concentrations. Comparative analyses with equipotent single-target inhibitors in metabolite supplementation approaches revealed that the dual-targeting mode represents the mechanistic basis for the potent antiviral activity. For SARS-CoV-2, an optimized dual inhibitor completely blocked viral replication in human airway epithelial cells at 5 nM and displayed a synergistic drug interaction with the nucleoside analog molnupiravir. In a SARS-CoV-2 mouse model, treatment with a dual inhibitor alone, or in combination with molnupiravir, reduced the viral load by 7- and 58-fold, respectively. Considering the clinical safety, oral bioavailability, and tolerability of izumerogant in a recent Phase I study, izumerogant-like drugs represent potent dual-targeting antiviral HDAs with pronounced broad-spectrum activity for further clinical development.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Broad-spectrum antiviral; DHODH inhibitor; Dual-targeting small molecules; Host-targeting antiviral; Human viruses; RORγ inhibitor